Application of The First Pillar of Community-Based Total Sanitation (Sanitasi Total Berbasis Masyarakat) With The Incidence Of Diarrhea Of Temon Kulon Village, Temon District, Kulonprogo - Hasna Atin Nafisah; Sigid Sudaryanto; Naris Dyah Prasetyawati (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
The goal of health development towards Healthy Indonesia in 2025 is the increase of awareness, willingness, and ability to live healthy for everyone. The main activity of Community-Based Total Sanitation Movement (STBM) is to change the behavior of the community for open defecation. Developing clean and healthy living behaviors in everyday life needs to be done to prevent the increasing incidence of environmental-based diseases, including diarrhea. The purpose of this study is to determine the effect of the implementation of first pillar of Community-Based Total Sanitation Program (STBM) with the incidence of diarrhea residents Temon Kulon , Temon, Kulonprogo. The type of the research was qualitative approach research design with descriptive cross sectional survey method. Population in this research was Temon Kulon village citizen of productive age that is age 17 - 60 year counted 1,002 people. The sample used in this study was 100 people taken 10% of the population. Based on the results of the research, it that community defecation behavior was good with 100% percentage. The condition and ownership of toilet had reached the results 100% of the people already had family toilet, 97% of the toilet condition of majority respondents were qualify, and the incidence of diarrhea was low because it was less than 50 people. It can be concluded that there is an influence between the implementation of the first pillar of Community-Based Total Sanitation (STBM) program with the incidence of diarrhea in ??Temon Kulon, Temon.